Legal Philosophy in Constructing the Pancasila Legal System in Indonesia - Putra Kaslin Hutabarat (Universitas of Muhammadiyah Makassar, 2022)
This research is based on the philosophical conception of Pancasila as the basic norm of law formation. Therefore, it is necessary to reconstruct a legal system that is in accordance with the noble values of a nation. Good law is a law that applies well from society as a long-lasting noble value from the ancestors of the community. This study uses a qualitative description method through the study of literacy in books and other scientific notes. The data analysis technique uses narrative analysis techniques. This research can be guaranteed in accordance with the meaning of the rule of law based on Pancasila, the paradigm of the development of the Indonesian legal state based on Pancasila, requiring the Indonesian legal state which is built on the basic values of divinity, humanity, unity, populist, and social justice.Penelitian ini didasari oleh konsepsi filosofis Pancasila sebagai norma dasar pembentukan hukum. oleh sebab itu, diperlukan rekonstruksi sistem hukum yang sesuai nilai luhur sebuah bangsa. Hukum yang baik adalah hukum berlaku baik dari masyarakat sebagai nilai luhur yang bertahan lama dari leluhur masyarakat. Penelitian ini menggunakan metode deskripsi kualitatif melalui studi literasi buku dan catatan ilmiah lainya. Teknik analisis data menggunakan teknik analisis naratif. Penelitian ini dapat disimpulkan sesuai dengan makna negara hukum berdasarkan Pancasila, Paradigma pembangunan negara hukum Indonesia yang berbasis Pancasila, mensyaratkan negara hukum Indonesia dibangun di atas nilai-nilai dasar ketuhanan, kemanusiaan, persatuan, kerakyatan, dan keadilan sosial.